A new species of Hypoganus Kiesenwetter, 1858 (Coleoptera: Elateridae: Dendrometrinae) from China, with notes on the Palaearctic species of the genus - Qiu, Lu; Prosvirov, Alexander S. (Zootaxa, 2017)
Hypoganus wennae sp. nov. is described and illustrated from Yunnan, China. Notes on the genus from the Palaearctic region are given. A distribution map of Chinese Hypoganus species is provided, along with a key and a checklist of the species from Palaearctic region. Habitats of Hypoganus species are illustrated.